Geological and technological characterization of the Late Jurassic-Early Cretaceous clay deposits (Jebel Ammar, northeastern Tunisia) for ceramic industry. (May 2017) - Ben M'barek-Jemaï, Moufida; Sdiri, Ali; Ben Salah, Imed; Ben Aissa, Lassaad; Bouaziz, Samir; Duplay, Joelle
Abstract: Late Jurassic-Lower Cretaceous clays of the Jebel Ammar study site were used as raw materials for potential applications in ceramic industry. Physico-chemical characterization of the collected samples was performed using atomic absorption spectroscopy, X-ray diffraction, thermogravimetry and dilatometry (Bugot's curve). Geotechnical study was also undertaken by the assessment of plasticity and liquidity limits. It was found that high concentrations of silica, alumina with SiO2 /Al2 O3 ratio characterized the studied clays; its high amounts of CaO and Fe2 O3 in the Late Jurassic clays indicated their calcareous nature. In addition, technological tests indicated moderate to low plasticity values for the Late Jurassic and Lower Cretaceous clays, respectively. Clay fraction (<2 μm) reached 50% of the natural clay in some cases. Mineralogical analysis showed that Jurassic clays were dominated by smectite, illite and kaolinite, as clay mineral species; calcite was the main associated mineral. Lower Cretaceous clays were mainly composed of abundant illite accompanied by well-crystallized smectite and kaolinite. Kaolinite gradually increased upwards, reaching 70% of the total clay fraction (i.e. <2 μm). Quartz, calcite and feldspar were the main non-clay minerals. Based on these analyses, the clays meet technological requirements that would allow their use in the ceramic industry and for the manufacturing of ceramic tiles. Highlights: Natural clay deposits of Jebel Ammar showed good physico-chemical properties. Tunisian natural clays are potentially utilizable in ceramic industry. Impurities influenced the firing behavior of natural clay. Ceramic tests on the raw clays gave encouraging results.